NORMATIVE GROUND OF THE JUDGEMENT OF MORAL OBLIGATION - H. Mitias, Michael (Journal of Dharma, 1979)
Can a judgment of moral obligation, e.g.,' 1 ought to do X, where X stands for a specific moral action, be true or false? Is such a judgment empirical, and if so, in what sense? What method or mental operation is involved in the verification of such a judgment This line of questioning arises because: (1) Unlike a scientific statement, which merely describes what is the case, a judgment of obligation is normative. It does not report a state of affairs; it prescribes an action in the future, and this quality of prescription is what makes normative, de jure judgment. The normative content, it is held, not empirical or sensuous in character. It is a unique kind of reality. Thus the question arises: whence does the judgment of obligation derive its power of prescription? Can we justify it empirically? Can we analyse 'ought' in terms of non-moral or factual predicates? For, if 'ought' designates a non-empirical source or principle, and if it is the ground of the judgment of obligation, then it would be extremely difficult, if not impossible, to say that the judgment amenable to empirical verification or that it is corrigible. (2) In making a judgment of obligation a person feels compelled, obliged, to perform a certain act. He feels that he ought to perform the act regardless of whether or not its consequences are pleasant or agreeable. This feeling, which seems to correspond to 'ought' qua unique reality, somehow becomes actual in the process of moral evaluation. So we ask: What is the source of this feeling? Is it distinctive and separate from the psycho-physical nature of the moral agent? Is it, for example, a faculty or sense naturally or divinely implanted in man?